Crystal growth in dentinal tubules with bio-calcium carbonate-silica sourced from equisetum grass - Hao-Hueng Chang; Chun-Liang Yeh; Yin-Lin Wang; Guan-Wen Liu; Hong-Ping Lin; Chun-Pin Lin (Journal of the Formosan Medical Association, 2020)
Background/Purpose: One effective way to deal with dentin hypersensitivity is to develop materials to seal the tubules. The porous bio-calcium carbonate-silica (BCCS) contained well-dispersed CaCO3 would form calcium phosphates to seal the dentinal tubules when mixed with an acidic solution. The acidic hydrothermal treatment and calcination to isolate the BCCS from the agricultural waste like equisetum grass was used, which would be more environmentally friendly than chemically synthesized mesoporous biomaterials. The aim of this study was to develop mesoporous materials from natural resources to occlude the dentinal tubules which could be more environmentally-friendly. Methods: Dentin disc samples were prepared and treated with different methods as follows: (1) BCCS mixed with H3PO4; (2) BCCS mixed with KH2PO4; (3) Seal & Protect® was used as a comparison group. Sealing efficacy was evaluated by measuring the depths and percentages of precipitate occlusion in dentinal tubules with SEM. Results: The N2 adsorption–desorption isotherm of the BCCS demonstrated a pore size of around 15.0 nm and a surface area of 61 m2g-1. From the results of occlusion percentage and depth, the BCCS treated with H3PO4 or KH2PO4 demonstrated promising sealing efficacy than the commercial product. Conclusion: This synthetic process used the agricultural waste equisetum grass to produce bio-calcium carbonate-silica would be environmentally friendly, which has great potential in treating exposed dentin related diseases.